2014
DOI: 10.1037/a0035071
|View full text |Cite
|
Sign up to set email alerts
|

Babies in traffic: Infant vocalizations and listener sex modulate auditory motion perception.

Abstract: Infant vocalizations and "looming sounds" are classes of environmental stimuli that are critically important to survival but can have dramatically different emotional valences. Here, we simultaneously presented listeners with a stationary infant vocalization and a 3D virtual looming tone for which listeners made auditory time-to-arrival judgments. Negatively valenced infant cries produced more cautious (anticipatory) estimates of auditory arrival time of the tone over a no-vocalization control. Positively vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, the current finding is likely the result of a well-documented difficulty in applying metric labels accurately to speed stimuli rather than a true perceptual underestimation of the speed of approach (Recarte et al, 2000; Recarte & Nunes, 1996; Triggs & Berenyi, 1982). For example, previous research using the same stimuli required participants to execute a button push when a looming sound source arrived and participants significantly underestimated arrival time indicating a perceived speed that was faster than actual (Neuhoff et al, 2014, 2012; Riskind et al, 2014). Because “labeling” the speed of looming sounds is typically not a priority in a natural environment, the primary concern here was to examine relative differences between conditions rather than absolute estimates of speed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the current finding is likely the result of a well-documented difficulty in applying metric labels accurately to speed stimuli rather than a true perceptual underestimation of the speed of approach (Recarte et al, 2000; Recarte & Nunes, 1996; Triggs & Berenyi, 1982). For example, previous research using the same stimuli required participants to execute a button push when a looming sound source arrived and participants significantly underestimated arrival time indicating a perceived speed that was faster than actual (Neuhoff et al, 2014, 2012; Riskind et al, 2014). Because “labeling” the speed of looming sounds is typically not a priority in a natural environment, the primary concern here was to examine relative differences between conditions rather than absolute estimates of speed.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies have identified specific neural mechanisms that preferentially process looming sounds over auditory motion in other directions (Bach et al, 2008, 2009, 2015; Seifritz et al, 2002). Sex differences and a correlation between physical fitness and the looming bias suggest that the bias is related to the ability to defend oneself in the face of a looming threat (Grassi, 2010; Neuhoff et al, 2009, 2012, 2014; Schiff & Oldak, 1990). Behavioral experiments show that listeners consistently err on the side of safety when perceiving auditory arrival time (Gordon & Rosenblum, 2005; Neuhoff, 2001; Rosenblum et al, 1987, 1993, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon that approaching sounds are more salient than receding sounds is commonly termed "auditory looming bias." Looming bias is reflected in a broad variety of psychophysical tasks related to salience and alertness: bias in loudness-change estimates (2-4) and judgments of duration (5), improved discriminability of motion speed (6), underestimated distances for egocentrically moving (4) or bypassing sounds (7,8), and reduced reaction time for auditory (3, 9) and visual (3) targets preceded by looming sounds. In animals, looming biases result in faster learning speed during associative conditioning (10) and longer duration of attention (11).…”
mentioning
confidence: 99%